Técnicas de relajación y atención en los niños de Primer año de Educación Básica de la Escuela de Educación Básica “Mercedes Amelia Guerrero”, del cantón Chambo. - Salguero Yasaca, Mariuxi Lizbeth (2024)
The research presents a study on the importance of the interest and participation of first year elementary school students in the learning process. It highlights the need to understand how students adapt and face challenges in order to develop strategies that support their attention and concentration capacity. In addition, the importance of implementing pedagogical techniques that encourage student engagement and address possible obstacles that may affect their attention during class. The relevance of intentionality to activate, focus and maintain attention on what is relevant for current or future learning is also mentioned. This research can serve as a basis for implementing pedagogical strategies that foster greater student engagement and address possible obstacles that may affect their ability during class. The present research uses a mixed approach that integrates the review of bibliographic sources to obtain a thorough understanding of the topic, also a non-experimental and cross-sectional field research is conducted to address the problem posed and proposing a solution without the need for experimental testing. The total population of 100% is 29 children, in which 52% are 14 boys and 48% are 12 girls, all of them students of the First Year of Basic Education of the School of Basic Education "Mercedes Amelia Guerrero".